Inversão gravimétrica estável do relevo da base e da variação da densidade com a profundidade em aterros sanitários - TEIXEIRA, Wlamir Abreu (Universidade Federal do Pará, 2014)
The present method assumes a decrease in the density contrast of a sedimentary basin according to a hyperbolic law in a waste landfill and uses two approaches: (1) the estimation of the bottom of a waste landfill assuming that the gravity anomaly, the density contrast at the surface and the decaying factor of the density contrast with depth are known; (2) the estimation of the density contrast at the surface and of the decaying factor of the density contrast with depth, assuming that the gravity anomaly and the relief of the waste landfill bottom are known. A variation of the latter approach consists in using the known depth values to the landfill bottom to produce a fitted gravity anomaly and estimate the density contrast at the surface and the decaying factor of the density contrast with depth via minimization of the Euclidean norm of the residual vector between the observed and fitted anomalies. In both cases the interpretation model is a set of vertical rectangular 2D prisms whose thicknesses are parameters to be estimated and represent the depth to the interface separating sediments and basement. The solutions of both problems are stable because of the incorporation of additional a priori information about the smoothness of the estimated relief. The presented method was applied to synthetic data produced by simulated waste landfills having maximum depth to the bottom smaller than 15 m and presenting smooth relief. The results were consistent and demonstrated the effectiveness of the method in both approaches. The method was also applied to the residual Bouguer anomaly from the Thomas Farm, Indiana, USA, leading to the conclusion that the density contrast of the landfill is either constant or present a maximum variation of about 0.09 g/cm3.